Spousal labour supply adjustments to extended benefits weeks: Evidence from Canada - Stephanie Lluis; Brian McCall (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
In this paper, we study the impact of increased unemployment insurance generosity in terms of additional weeks of benefits on a spouse's labour supply adjustments after the job loss of his/her partner. We exploit the longitudinal household format of the Canadian Labour Force Survey and the Survey of Labour and Income Dynamics to study the labour force transitions of each spouse over time and spousal labour supply responses arising from an added worker effect, whereby spousal labour supply increases following the partner's job loss. We examine whether the additional weeks of benefits offered by the Extended Weeks (EW) pilot, an initiative of the Employment Insurance program implemented in a subset of regions, had a differential impact on spousal labour supply adjustments. Employing a difference-in-differences (DiD) approach, the crowding-out effect of this increased EI generosity on spousal labour supply is identified. Our fixed-effect estimation results show a statistically significant added worker effect for women of 14 to 17 hours weekly following their partner's job loss if they are not eligible to receive EI benefits. The eligibility of employment insurance benefits reduces spousal labour supply among women by 3 to 6 hours per week, with a stronger effect among mothers.
Keywords: J62; J65; 330; Employment Insurance; Unemployment Insurance Weeks; Spousal LabourSupply; Added Worker Effect; Crowding-Out Effect